Association of Hyperuricemia with Hypertension in a Tertiary Hospital of Karachi - Mishal Haroon, Rida Malik, Urooj Riaz, Ajeet Kumar, Monika Kumari, Farina Zameer (Pakistan Journal of Medical & Health Sciences, 2024)
Objective: To determine the frequency of hyperuricemia in hypertensive patients admitted to a tertiary healthcare hospital of Karachi. Methodology: This study was conducted in Sohail Trust Hospital in Department of Medicine. It was a cross sectional study. Duration was 6 months from 13th March, 2023 to 13th September, 2023. All patients who fulfilled the inclusion criteria in the department of General Medicine, Sohail Trust Hospital, Karachi, were included in the study. After taking informed written consent, history was taken, clinical examination was done and serum uric acid level was checked to reach the outcome i.e. hyperuricemia. Result: A total of 235 patients with hypertension were included. 159 patients (67.7%) were males & 76 patients (32.3%) were females with the mean age of 57.540+8.459 years. Hyperuricemia was seen in 143(60.9%) patients. Conclusion: In conclusion the frequency of hyperuricemia was high in hypertensive patients. It increases with the increase in age, duration of hypertension and predominant in male gender. The trend in low socio-economic class was hence found to be similar. Keywords: Hyperuricemia, risk factor, hypertension